Ayush Fashion : the expansion dilemma - Yousaf, Anish; Dey, Subhendu; Mishra, Abhishek (Professor of Law) (London : Neilson Journals Publishing, 2019)
Ayush Fashion Private Limited saw strong growth in sales volumes in its girlswear (age 1-16 years) garment market over the past few years. Under the visionary leadership of its chairperson, Jaya Bakshi, and supporting capable management, led by the managing director Ajay Chopra, Ayush had become a household name in the northern parts of India for producing garments in the premium category.1 However, in the last three years, a substantial decline in its profits created concern for the management. After a series of deliberations, the board of directors considered three options to contain the decline in profits: (1) expand into the boyswear category for the same age group, (2) expand into the womenswear category for the age group 16-40 years, and (3) no expansion, but focus on cost reduction. The case enables students to appreciate the challenges of line extension, product/market development, and the importance of strategic decision making for mid-sized firms in a situation which requires a rapid course of correction.
Originally Published In Yousaf, A., Dey, S., & Mishra, A. (2019). Ayush Fashion - The Expansion Dilemma. Journal of International Business Education, 14(1), 373-388. JIBE14-0CS5.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Clothing trade -- India -- Case studies